PARTISIPASI MASYARAKAT DALAM PELESTARIAN DANAU TONDANO DI KABUPATEN MINAHASA - Herling A Watania; Ellen Eva Poli; Xaverius Erick Lobja (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2021)
The research objective was to determine and describe how the participation and role of the community around Lake Tondano to preserve Lake Tondano from the silting process. To get accurate data, there are several ways to collect data which are often called data collection techniques, including (1) Interview, (2) Observation, (3) Documentation study. This research uses qualitative methods with qualitative descriptive analysis, namely by collecting, managing, presenting, and describing the research results as they are. Based on the results of the research, it is known that the form of community participation in the rehabilitation of Lake Tondano includes: (a) Community participation in the South Tondano sub-district is actively planting replacement trees around the lake, making terraces in the hills around the lake, continuous socialization to the community around the lake, and The community no longer throws plastic waste into waterways, either sewers or rivers, so that the lake ecosystem is maintained. Another participation is that the local community is also obliged to provide information to the sub-district or village government if there are people who try to destroy the forest carelessly around the lake and people who deliberately dump plastic waste on a large scale into waterways in the form of ditches and rivers. Also, the local community has followed government regulations regarding the preservation of Lake Tondano; (b) Other types of participation contributed by the community in South Tondano sub-district, including; a) participation of ideas or ideas, b) participation of personnel, c) participation of assets, d) participation of skills and skills and e) social participation. Forms of community participation in the environmental conservation of Lake Tondano are in the form of; a) active participation, b) passive participation.